Obtención de una agente desinfectante a partir de la electrólisis de cloruro de sodio para el tratamiento de agua potable (2018)
The objective of this degree work is to obtain a disinfectant agent for sodium chloride electrolysis to evaluate its application in drinking water, this is due to the fact that it is difficult to carry out drinking water in rural areas, coastal areas of the country. , and the absence of adequate mechanisms to adopt a comprehensive system that covers the entire population, in addition to the risks involved in transporting and handling the most used disinfectants. The development of the project was carried out in three phases: the first phase was the investigation of the variables involved in the sodium chloride electrolysis technique, and from which the determining variables and the control variables for the development of this technique were determined ; additionally, the operating conditions were specified through a bibliographic reference matrix, which allowed the growth of the design of experiments where the salt concentration, the current density and the agitation are three factors and each one has three levels of operation.